How do artificial neural networks lead to developing an optimization method? - Sadollah, Ali (Trends in Computer Science and Information Technology, 2020)
This concise paper explains the inspiration of AI particularly artificial neural networks (ANNs) for developing new metaheuristics. Using the unique concept of ANNs and its wide applications in different fields of study, how the ANNs can be utilized for solving real life and complex optimization problems? This paper briefly links the inspiration to a practical model in order to build an optimization strategy.